Challenges and threats to implementing the fight against doping in sport - Dvorak, J.; Saugy, M.; Pitsiladis, Y. P. (British Journal of Sports Medicine, 2014)
Prominent doping cases in certain sports have recently raised public awareness of doping and reinforced the perception that doping is widespread. Efforts to deal with doping in sport have intensified in recent years, yet the general public believes that the `cheaters` are ahead of the testers. Therefore, there is an urgent need to change the antidoping strategy. For example, the increase in the number of individual drug tests conducted between 2005 and 2012 was approximately 90 000 and equivalent to an increase of about 50%, yet the number of adverse analytical findings remained broadly the same. There is also a strikingly different prevalence of doping substances and methods in sports such as a 0.03% prevalence of anabolic steroids in football compared to 0.4% in the overall WADA statistics. Future efforts in the fight against doping should therefore be more heavily based on preventative strategies such as education and on the analysis of data and forensic intelligence and also on the experiences of relevant stakeholders such as the national antidoping organisations, the laboratories, athletes or team physicians and related biomedical support staff. This strategy is essential to instigate the change needed to more effectively fight doping in sport.